(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
The cultivation of Pleurotus ostreatus mushrooms has gained popularity in the Philippines because of its ability to grow across a wide range of temperatures and to utilize diverse lignocellulosic substrates. However, optimizing culture conditions is essential for improving the growth efficiency of sporeless strains, which are preferred due to reduced health risks and better quality of mushroom products. This study aimed to determine the optimum cultural conditions for the mycelial growth of P. ostreatus (sporeless strain) by evaluating the effects of media type, pH level, aeration (sealed vs. unsealed plates), illumination (dark, light, or alternating dark/light), and incubation temperature. Mycelial growth was assessed across five different culture media and varying environmental conditions. Results revealed that rice bran decoction gulaman supported the most favorable growth, with near-neutral to slightly basic pH, under sealed or non-aerated conditions. Growth was consistent across dark, light, or alternating illumination, and was optimal at both room temperature and air-conditioned settings. These findings demonstrate that the sporeless strain exhibits strong adaptability to diverse conditions, reducing cultivation constraints compared with spore-forming counterparts. This research establishes the specific cultural requirements for the sporeless strain, which has been less studied despite its advantages. Optimizing its growth conditions can enhance mushroom production efficiency, minimize spore-related health risks for growers, and promote sustainable utilization of local agro-industrial byproducts, contributing to food security and rural livelihood development. This research supports SDGs by contributing to SDGs 2 (Zero Hunger) through improved mushroom production efficiency and food security; SDGs 3 (Good Health and Well-being) by reducing spore-related occupational health risks; SDGs 8 (Decent Work and Economic Growth) by strengthening livelihood opportunities in small-scale enterprises; SDGs 12 (Responsible Consumption and Production) through the sustainable use of agro-industrial byproducts; and SDGs 13 (Climate Action) by promoting resource-efficient cultivation practices aligned with the sustainability framework of the United Nations Sustainable Development Goals.